Chasing light : Michelle Obama through the lens of a White House photographer - Lucidon, Amanda (Ten Speed Press, 2017)
"A collection of striking and intimate photographs of Michelle Obama--many never before seen--coupled with personal reflections and behind-the-scenes stories from Official White House Photographer Amanda Lucidon, presented in a deluxe format. Michelle Obama is one of the most admired First Ladies in history, known for her grace, spirit, and beauty, as well as for the amazing work she did during her tenure to promote girls' education, combat childhood obesity, and support military families. In Chasing Light, former White House photographer Amanda Lucidon, who spent four years covering the First Lady, shares a rare insider's perspective, from documenting life at the White House to covering domestic and overseas travel. This collection of 150 candid photos--many previously unreleased--and Amanda's narrative reflections reveal just what makes Mrs. Obama so special. From an affectionate moment with her daughters atop the strikingly empty Great Wall of China to exuberant moments with schoolchildren and quiet moments between the First Lady and President Obama, the photos are a vibrant, candid, and beautiful celebration of the First Lady, capturing the qualities and strengths that have made Mrs. Obama so beloved"--